Euro Area Policies : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Member Countries. (IMF Staff Country Reports; Country Report ;, 2018)
This is a time to strengthen the resilience of the euro area and raise its long-term growth potential. Despite the recent slowdown and coming end of quantitative easing, growth remains strong and monetary conditions accommodative. Member countries should grasp the opportunity to address deep structural challenges, rebuild thin policy buffers, and rebalance externally. Mounting downside risks add urgency. The supportive monetary stance should be maintained until inflation is convincingly converging to objective. As net asset purchases draw to a close, clear forward guidance will become even more important.